Modelo ProLab, propuesta de plataforma digital to office de alimentos saludables para los oficinistas de Lima - Rivas Arribasplata, Ana María Sara (2024)
This report proposes a financially and socially sustainable business idea to solve a Relevant Social Problem (RSP) that directly affects office workers in the districts of Miraflores, San Borja and San Isidro. The Design Thinking methodology and others were used to develop the project. In this way, it was identified that in many companies in Lima, office workers have difficulties in acquiring healthy food, thus affecting their health and well- being, leading them to consume food that is not very nutritious. The problem is related to Sustainable Development Goals 2, 3 and 12 focused on nutrition, health and sustainability. The proposed solution consists of the development of an application that offers healthy food through a dark kitchen business model as well as the possibility of obtaining virtual and face- to-face nutritional counseling. Through digital surveys, the desirability of users for the solution was validated. After an analysis that considered an annual growth of 30% in the number of clients, it was determined that the project has financial viability since the economic NPV obtained in an expected scenario was positive with a value of S/. 3,251,150. On the other hand, a social NPV was obtained for a value of S/. 13,365,533 which demonstrated the social viability of the project. Finally, it is concluded that the proposal is scalable since the solution could be extended to more districts of Lima, as well as nationally.